Thiamine fortification strategies in low‐ and middle‐income settings: a review. Issue 1 (26th January 2021) - Whitfield, Kyly C.; Smith, Taryn J.; Rohner, Fabian; Wieringa, Frank T.; Green, Tim J.
Abstract: Thiamine (vitamin B1 ) is an essential micronutrient in energy metabolism and cognitive and neurological health. Thiamine deficiency disorders (TDDs) have a range of clinical presentations that result in various morbidities and can be fatal if not promptly recognized and treated, especially in infants. To intervene, thiamine intakes by breastfeeding mothers and others at risk of thiamine deficiency should be increased to ensure adequate thiamine intake. Although thiamine fortification programs have a long history in high‐income countries, there are few mandatory fortification programs to address TDDs in low‐ and middle‐income countries (LMICs), particularly in the regions of greatest concern, South and Southeast Asia. This review highlights essential aspects for consideration in the development of a mandatory fortification program in LMICs, including an overview of the data required to model fortification dosing schemes, available thiamine fortificants, and potential fortification vehicles, as well as identifies current knowledge gaps. Abstract : There are few mandatory fortification programs to address thiamine deficiency disorders in low‐ and middle‐income countries (LMICs), particularly in the regions of greatest concern, South and Southeast Asia. This review highlights essential aspects for consideration in the development of a mandatory fortification program in LMICs, including an overview of the data required to model fortification dosing schemes, available thiamine fortificants, and potential fortification vehicles, as well as identifies current knowledge gaps.